Pirolisis Kayu Ketapang (Terminalia Catappa) Menjadi Bio-Oil Menggunakan Katalis Mo/NZA - Ridho Fahrozi; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Petroleum is explored and consumed everyday, while the formation process takes millions of years. Therefore, it need alternative energy which not dependent on fossil resources and can be renewable, one of them is to produced bio-oil from biomass. One of the potential biomass which used as raw material for bio-oil is Terminalia catappa. Biomass can be converted to bio-oil by the way of pyrolysis. The purpose of this study determine the effect of developing of metal (0%, 0.5%, 1% and 1.5%) and variation of Mo/NZA catalyst to produce bio-oil and characterized the physical and chemical properties bio-oil. Pyrolysis of Terminalia catappa with Mo/NZA catalyst in the slurry reactor has been done by feeding 50 grams of Terminalia catappa with the size -100+200 mesh, silinap 500 ml, variation in levels of catalyst 1%, 2%, 3% w/w of the feedstock, at 320oC for 120 minutes. The results showed that the optimum yield obtained on 0.5% Mo/NZA catalyst in level of catalyst 3%, amounting to 68.53%. The test results showed that the physical properties of density 0.979 g/ml, viscosity 3.27 cSt, flash point 52°C and acidity 48.49 mg NaOH/gram of sample. The results of chemical analysis by GC-MS, obtained the dominant chemical components in bio-oil were acetaldehyde 6,98%; acetic acid 58.42%; 2-propanone 11.04%; propanoic acid 4.36% and 2-furancarboxaldehyde 5.55%.Keywords: Alternative energy, Biomass, Bio-oil, Mo/NZA, Pyrolysis, Terminalia catappa